Koordinasi Badan Narkotika Nasisonal Kabuapten (BNNK) dalam P4GN (Pencegahan, Pemberantasan, Penyalahgunaan dan Peredaran Gelap Narkoba) di Kabupaten Tojo Una-Una - Djanatu, Yusrin A.; Katili, Andi Yusuf; Djabah, Misbahudin (Innovative: Journal Of Social Science Research, 2024)
The purpose of this research is to find out how to build effective communication for the parties involved, to find out what factors cause differences in goals and priorities and how to align these goals, and to find out how to increase active community participation in planning and implementing the P2M program. Data collection uses observation, interviews and documentation methods. Stages of data analysis through data reduction, data preparation, and drawing conclusions. The research results show that communication between the Tojo Una-Una BNNK and several agencies in implementing the P4GN program in Tojo Una-Una Regency is considered less effective. This is caused by a lack of seriousness on the part of the Tojo Una-Una BNNK in carrying out the P4GN program, and the program being launched is still monotonous and has not been adapted to current developments. Factors causing differences in goals and priorities at the Tojo Una-Una BNNK include: openness of public information in reporting narcotics abusers, a lack of Tojo Una-Una BNNK personnel in the field, and a minimal program budget. To increase active community participation in planning and implementing the P2M program, BNNK Tojo Una-Una implemented four main strategies consisting of Soft Power Approach, Hard Power Approach, Smart Power Approach, and Cooperation.